2021
DOI: 10.4054/demres.2021.44.38
|View full text |Cite
|
Sign up to set email alerts
|

The social context of retrospective-prospective changes in pregnancy desire during the transition to adulthood: The role of fathers and intimate relationships

Abstract: BACKGROUNDResearchers have questioned the accuracy of retrospective measures of unintended pregnancy, which ask women whether they wanted a pregnancy before it was conceived. OBJECTIVEWe investigated whether pregnant women's retrospective recollections of their preconception desires for pregnancy were shaped by intimate relationships, their own reactions, and their perceptions of their partners' reactions to their pregnancies. METHODSWe used the Relationship Dynamics and Social Life (RDSL) study, which include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Researchers use these data to classify pregnancies -and the resulting births -as intended or unintended (Gipson, Koenig, and Hindin 2008). Research has shown, however, that intentions measured after birth differ from a mother's report about the same pregnancy before conceiving or while pregnant (Barber and Gatny 2021;Bishai et al 2015;Joyce, Kaestner, and Korenman 2000;Koenig et al 2006;Rosenzweig and Wolpin 1993). Expost rationalization, recall bias, and social desirability bias may drive mothers to report a pregnancy as intended, regardless of whether it was.…”
Section: Data and Design Challenges For Understanding The Consequences Of Unintended Births For Women's Healthmentioning
confidence: 99%
“…Researchers use these data to classify pregnancies -and the resulting births -as intended or unintended (Gipson, Koenig, and Hindin 2008). Research has shown, however, that intentions measured after birth differ from a mother's report about the same pregnancy before conceiving or while pregnant (Barber and Gatny 2021;Bishai et al 2015;Joyce, Kaestner, and Korenman 2000;Koenig et al 2006;Rosenzweig and Wolpin 1993). Expost rationalization, recall bias, and social desirability bias may drive mothers to report a pregnancy as intended, regardless of whether it was.…”
Section: Data and Design Challenges For Understanding The Consequences Of Unintended Births For Women's Healthmentioning
confidence: 99%
“…Retrospective measures of fertility may also be subject to social desirability bias insofar as mothers may engage in postpartum rationalizations or by an unwillingness to admit that a now loved child was a “mistake.” Prospective studies that ask women if they intend to have a(nother) child and then follow up to see if they do in fact have children (Rackin and Morgan 2018) may reduce problems of recall and social desirability bias. Prospective measures, however, can overestimate the unintended pregnancy rate because women change their fertility intentions over the life course with changing social contexts (Barber and Gatny 2021; Hayford 2009; Iacovou and Tavares 2011; Ní Bhrolcháin, Beaujouan, and Berrington 2010; Rackin and Morgan 2018). Rackin and Morgan (2018) recommended using retrospective measures to assess unintended pregnancies (in part because these measures do not require longitudinal data), but prospective measures may be more appropriate when the goal of the research is to predict future behavior (e.g., having a baby) (Moreau et al 2013).…”
Section: Introductionmentioning
confidence: 99%